Characteristics of Mandibular Movement and Mastication in Older Adults with Removable Dental Prostheses: Three-Dimensional Analysis - Rivera, Paloma; Farfán, Constanza; Arias, Alain; Lezcano, María Florencia; Dias, Fernando José; Navarro, Pablo; Fuentes, Ramón
Aging is a dynamic process that includes various alterations in the oral cavity, with tooth loss being the most frequent. Rehabilitative treatment may include removable or fixed prostheses and implants. The aim of this study was to describe the geometric (trajectory, ranges, areas) and kinematic (speed) characteristics of the mandibular and masticatory movements threedimensionally in participants with dental prostheses. A sample of 10 participants with removable prosthetic rehabilitation was divided into three groups (complete, atypical and overdenture) the characteristics of mandibular movements bordering and chewing with 3D Electromagnetic Articulography were measured. The Posselt polygonin was obtained, the frontal and sagittal plans, its areas, trajectories and ranges are analyzed. The masticatory movements were analyzed in the area of each cycle, the frequency, the speed and the reason between the masticatory cycle and the bordering movements, no significant differences between the groups. Subjects with dental prostheses, regardless of the type, they showed low of motion (border and functional) compared to dentate subjects with no functional alterations whose values have been reported in the literature. The subjects with overdenture have values closer to what is described for young dentate subjects.